KONSISTENSI MASYARAKAT ADAT TERHADAP TATANAN FISIK SPASIAL KAMPUNG ADAT CIREUNDEU, CIMAHI SELATAN - Nadya Sherlinda; Yohanes Basuki Dwisusanto (Riset Arsitektur (RISA), 2023)
Abstract - Cireundeu Traditional Village is one of the traditional villages that still exist today. Located in Leuwigajah Village, South Cimahi District, Cireundeu Traditional Village has Sunda Wiwitan as the root of indigenous identity. Like a traditional village, there are many traditions, cultures, ancestral values, and rules handed down by previous elders. However, the rapid flow of globalization that is currently happening can have an impact on the meaning of customary values ​​in the Cireundeu Traditional Village. “Miindung ka time, mibapa ka era” – is one of the established principles which means that humans must grow and develop by following the progress of the times while still preserving the inherited culture. The existence of this principle makes the indigenous people of the Cireundeu Traditional Village open to the development of the times. This openness can affect the meaning of existing customary values, especially regarding village arrangements and patterns of spatial arrangement in buildings. The purpose of this study was to examine the consistency of the arrangement, as well as the customary values ​​of buildings with a residential scale in the indigenous people of the Cireundeu Traditional Village. The research was conducted with the hope of exploring what is behind the arrangement of the Cireundeu Traditional Village and how the consistency of indigenous peoples is in following the arrangement. The research was conducted using a descriptive method with a qualitative approach. Data collection was carried out by direct observation in the field, conducting interviews with figures who were considered to understand the history of the Cireundeu Traditional Village, and searching for secondary data using literature studies from previous research so that previous documentation about the Cireundeu Traditional Village could be obtained. Based on the collected data, it is concluded that the arrangement of the Cireundeu Traditional Village is based on the applicable rules and regulations regarding the placement of the main door and side door. Based on virtual documentation that was traced in 2006, 2010, 2013, 2017, 2019, and 2022, not much has changed. Although the form of housing is not in the form of a house on stilts, the indigenous people of the Cireundeu Traditional Village still interpret traditional values ​​through the application of the Pancawara concept. Thus, it is concluded that although the indigenous peoples are open to rapid development, the indigenous people of the Cireundeu Traditional Village are still consistent in maintaining traditional values. The application of these traditional values ​​of course undergoes several adjustments with the progress of the times. However, it can still be expressed through physical and spatial arrangements both at the village scale and at the residential scale. Keywords: traditional village, Pancawara, Cireundeu Traditional Village, Sunda Wiwitan